(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Over the past eight decades, numerous research has been conducted on the extraction of Zingiber zerumbet rhizome. The mini-review includes information on the pharmacological properties of zerumbone extracted from Z. zerumbet rhizome and the extraction methods conducted over the previous 80 years. Zerumbone is recognised as having a proven pharmacological effect and is a significant medicinal component used to treat various ailments. The pharmacological values are stated based on the research findings. The extraction method and technology are essential to extract zerumbone. Thus, the review helps the reader keep up with the history of each technique or technology used in extracting zerumbone from Z. zerumbet rhizome, starting with conventional technology and moving toward advanced technology.